Гіпертрофія лівого шлуночка у хворих на активну акромегалію: клініко-біохімічні та клініко-гормональні кореляти - Микитюк, М. Р.; Хижняк, О. О. (Clinical Endocrinology and Endocrine Surgery, 2014)
Examined 76 (26 men and 50 women) patients with active acromegaly aged from 20 to 70 years, average age 48.22±12.19 years. Echocardiographic signs of hypertrophy of the left ventricular (LVH) revealed in 63.2% of patients, including 46.0% – concentric LVH. Found that high levels of pituitary growth hormone (GH) and insulin like growth factor-1 (IGF-1) were independent predictors of LVH. Influence of GH and IGF-1 on the formation of LVH mediated through anthropometric parameters and levels of systolic and diastolic blood pressure, which are predictors in patients with acromegaly LVH.